EPIDEMIOLOGICAL PROFILE OF LEPROSY CASES AND DEATHS IN MATO GROSSO: 2011-2020 - Cristofolini, Carla Andressa; Cruz, Pietra Nascimento; Arruda, Vilmeyze Larissa de; Lima, Jaqueline Costa; Dominguez, Omar Ariel Espinosa; Silva, Pãmela Rodrigues de Souza (Cogitare Enfermagem, 2024)
Objective: To characterize the epidemiological profile of leprosy cases and deaths in Mato Grosso - Brazil, from 2011 to 2020. Method: A population-based observational study of all leprosy cases and deaths reported between 2011 and 2020. Subsequently, the reported individuals were matched, and the trend was estimated using the Prais-Winsten regression. Results: 37,623 new cases were registered in the study years, with an average rate of 114.7/100,000 inhabitants, with higher incidence rates in multibacillary cases and males, and in the proportion of deaths (58%; 88.2%), respectively. As for the trend, it has increased over the years and among women. Conclusion: The results suggest a profile of more incident cases, possible areas with the spread of the disease, and delayed diagnosis, highlighting the need to use indicators to monitor the endemic and strengthen comprehensive care and surveillance of leprosy.